a) (+5a²) + (-3a²) =
b) (+8x) - (-3x) =
c) (-5x) - (-11x) =
d) (-6y) - (-y) =
a ) 1by 15by
----- + ----- =
2 6
b) 32cz³ + 24cz³ =
c) Determine o valor da expressão algébrica 2x^4 + 4x - 5 com x = 3
Respostas
respondido por:
0
a)
= (+5a²) + (-3a²)
= 5a² - 3a²
= 2a²
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
b)
= (+8x) - (-3x)
= 8x + 3x
= 11x
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
c)
= (- 5x) - ( - 11x)
= - 5x + 11x
= 6x
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
d)
= (-6y) - (-y)
= - 6y + y
= - 5y
********************************
a )
1by 15by 3by + 15by = 18by
----- + --------- = ------------------ ---------- = 3by
2 6 6 6
*************************************
b) 32cz³ + 24cz³ = 56 cz³
******************************************
c) Determine o valor da expressão algébrica 2x^4 + 4x - 5 com x = 3
2x⁴ + 4x - 5 = 2.(3)⁴ + 4.3 - 5 = 2.81 + 12 - 5 = 162 + 7 = 169
= (+5a²) + (-3a²)
= 5a² - 3a²
= 2a²
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
b)
= (+8x) - (-3x)
= 8x + 3x
= 11x
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
c)
= (- 5x) - ( - 11x)
= - 5x + 11x
= 6x
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
d)
= (-6y) - (-y)
= - 6y + y
= - 5y
********************************
a )
1by 15by 3by + 15by = 18by
----- + --------- = ------------------ ---------- = 3by
2 6 6 6
*************************************
b) 32cz³ + 24cz³ = 56 cz³
******************************************
c) Determine o valor da expressão algébrica 2x^4 + 4x - 5 com x = 3
2x⁴ + 4x - 5 = 2.(3)⁴ + 4.3 - 5 = 2.81 + 12 - 5 = 162 + 7 = 169
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás